THE ECOLOGICAL FOUNDATIONS OF DHARMA: INVESTIGATING THE MEANING OF BEING HINDU - Parashar, Manan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article builds upon previous studies that have argued ecological consciousness as being central to the ancient Vedic (and modern Hindu) way-of-life. Differentiation between the terms ‘religion’, ‘culture’ and ‘dharma’ have been formalized. Hindu dharma has been defined in terms of its main objective: attaining moksha (liberation), and then investigated in terms of the rituals and practices that represent the belief-system of its followers. The ecological foundations of the ashrama and varnashrama (caste) systems have been investigated. Education-based policy recommendations for the protection of Hindu dharma have been presented in the conclusion.